2020
DOI: 10.1111/nyas.14315
|View full text |Cite
|
Sign up to set email alerts
|

Sex as a biological variable in the rat model of diisopropylfluorophosphate‐induced long‐term neurotoxicity

Abstract: Sex differences in response to neurotoxicant exposure that initiates epileptogenesis are understudied. We used telemetry-implanted male and female adult rats exposed to an organophosphate (OP) neurotoxicant, diisopropylflourophosphate (DFP), to test sex differences in the severity of status epilepticus (SE) and the development of spontaneous recurrent seizures (SRS). Females had significantly less severe SE and decreased epileptiform spikes compared with males, although females received a higher dose of DFP th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 71 publications
4
41
0
Order By: Relevance
“…EEG recordings from a separate cohort of animals confirmed DFP-induced neurological hyperactivity and increased spiking events in each sex and supported the observations of more severe behavioral seizures in males relative to females. Notably, the behavioral seizure response observed in our juvenile rat DFP model is less severe than has been previously reported for adult rat DFP models using nearly identical seizure scales ( Gage et al, 2020 , Supasai et al, 2020 ), suggesting age-specific seizure responses to DFP. This interpretation is supported by a recent publication that found seizure susceptibility to DFP increased significantly with age, ranging from the early postnatal period into young adulthood ( Scholl et al, 2018 ).…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…EEG recordings from a separate cohort of animals confirmed DFP-induced neurological hyperactivity and increased spiking events in each sex and supported the observations of more severe behavioral seizures in males relative to females. Notably, the behavioral seizure response observed in our juvenile rat DFP model is less severe than has been previously reported for adult rat DFP models using nearly identical seizure scales ( Gage et al, 2020 , Supasai et al, 2020 ), suggesting age-specific seizure responses to DFP. This interpretation is supported by a recent publication that found seizure susceptibility to DFP increased significantly with age, ranging from the early postnatal period into young adulthood ( Scholl et al, 2018 ).…”
Section: Discussionsupporting
confidence: 43%
“…This is consistent with literature demonstrating increased expression of cholinergic and glutamatergic receptors between the post-weaning period (∼PND 28) and early adulthood (∼PND 60) in rats ( Akazawa et al, 1994 , Monyer et al, 1994 , Jett, 1998 ). Although EEG activity was only recorded from a small cohort of animals that were not scored for seizure behavior, it has been demonstrated that seizure behavior is highly correlated with electrographic seizure activity in both male and female models of acute OP intoxication ( Tanaka et al, 1996 , McDonough and Shih, 1997 , Gage et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations